The Role of Environmental Law in Controlling the Exploitation of Natural Resources - Muh. Ramli; Ahmad Fadli; Priyanto; Marzuki Irham; Riyan Adnan Wahyudi (Journal AGENCY, 2026)
Uncontrolled exploitation of natural resources (NR) has become one of the major challenges to environmental sustainability, resulting in ecosystem degradation, environmental pollution, biodiversity loss, and increasing social conflicts over resource utilization. These issues have highlighted the urgent need for an effective legal framework capable of balancing economic development with environmental protection. Environmental law plays a strategic role in regulating the utilization and management of natural resources by establishing legal standards, preventive measures, and enforcement mechanisms that promote sustainable development. This study aims to analyze the role of environmental law in controlling natural resource exploitation in Indonesia and to evaluate the effectiveness of its implementation in achieving environmental sustainability. The research employs a normative juridical method using statutory and conceptual approaches through the analysis of relevant legislation, legal doctrines, and scholarly literature. The findings reveal that Indonesia’s environmental legal framework provides several important control instruments, including environmental licensing, Environmental Impact Assessment (EIA/AMDAL), environmental monitoring, and administrative, civil, and criminal sanctions for legal violations. Nevertheless, the implementation of these legal instruments continues to face significant challenges, such as weak law enforcement, overlapping regulations, limited institutional coordination, and low public awareness and participation in environmental protection. Therefore, strengthening regulatory frameworks, enhancing law enforcement capacity, and encouraging greater public participation are essential to achieving sustainable natural resource management and long-term environmental conservation in Indonesia.